The Effect Of Massed Practice And Distributed Practice On The Ability In Dribbling In Football Game - Muhammad Muhajirin; Sugeng Purwantu (Lembaga Penelitian dan Pendidikan Mandala, 2019)
This research aims to reveal: (1) effect differences between massed and distributed practice method on the ability in dribbling, (2) effect difference among players with high eye-foot coordination and low eye- foot coordination on the ability in dribbling, and (3) the significant interaction between the massed and distributed practice method as well as the eye-foot coordination on the ability in dribbling of the footballers of Green Boys FC Selengen ages 12-17 years. This research is an experiment with 2 x 2 factorial design. The population was 37 footballers of Green Boys FC Selengen ages 12-17 years. This research sample was 37 footballers estabilished using the random sampling technique. The instruments to measure eye-foot coordination was Mithcel Soccer Test and the test to measure dribbling ability was test of Nurhasan (2011). The data analysis technique used was two-way ANOVA at the level α = 0.05. The results are as follows. (1) There is a significantly different effect of massed and distributed practice method on the ability in dribbling in the game of football of footballers of Green Boys FC Selengen ages 12-17 years. The distributed practice method is better than massed practice method. (2) There is a significantly different effect of the ability of the eye-foot coordination and low eye-foot coordination on the ability in dribbling in the game of football of the footballers of Green Boys FC Selengen ages 12-17 years. The players with the high ability in high eye-foot coordination compared to those with the ability of the low eye-foot coordination. (3) There is a significant interaction between massed and distributed practice method with high eye-foot coordination and low eye- foot coordination on the ability in dribbling in the game of football of the footballers of Green Boys FC Selengen ages 12-17 years.